Exercise tolerance in obese vs. lean adolescents: a systematic review and meta‐analysis. Issue 11 (6th August 2014) - Hansen, D.; Marinus, N.; Remans, M.; Courtois, I.; Cools, F.; Calsius, J.; Massa, G.; Takken, T.
Summary To prescribe feasible and medically safe exercise interventions for obese adolescents, it remains to be determined whether exercise tolerance is altered and whether anomalous cardiopulmonary responses during maximal exercise testing are present. Studies that examined cardiopulmonary responses to maximal exercise testing in obese adolescents were searched: cardiopulmonary exercise tests with respiratory gas exchange measurements of peak oxygen uptake (VO2peak) were performed and comparisons between obese and lean adolescents were made. Study quality was assessed using a standardized item list. By meta‐analyses VO2peak, peak cycling power output (Wpeak) and peak heart rate (HRpeak) were compared between groups. Nine articles were selected (333 obese vs. 145 lean adolescents). VO2peak (L min−1), HRpeak and Wpeak were not different between groups (P ≥ 0.10), while a trend was found for a reduced VO2peak (mL min−1 kg−1 lean tissue mass) (P = 0.07) in obese vs. lean adolescents. It remained uncertain whether anomalous cardiopulmonary responses occur during maximal exercise testing in obese adolescents. In conclusion, a trend was found for lowered VO2peak (mL min−1 kg−1 lean tissue mass) in obese vs. lean adolescents. Whether cardiopulmonary anomalies during maximal exercise testing would occur in obese adolescents remains uncertain. Studies are therefore warranted to examine the cardiopulmonary response during maximal exercise testing in obese adolescents.